MANGELOLA KONFLIK LINGKUNGAN HIDUP DALAM RANGKA MEWUJUDKAN PEMBANGUNAN DAERAH SECARA BERKELANJUTAN - Suhardjana, Johannes (Bumi Lestari Journal of Environment; Vol 9 No 2 (2009), 2009)
Sustainable Development and Eco-Development are not the final aim which be reached in environment management. Meanwhile, the final purpose of environment management is welfare of human life on this time and future. Development on managing and exploiting Environment, beside can improve the society prosperity also contain potency as conflict source among the society. Management of environment conflict to realize the sustainable local development can be done by counselling and education, economic instrument in the form of incentive and disinsentif, and also through alternative dispute resolution.
Keywords: development; sustainable; welfare; environment